PENGARUH PELATIHAN GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. PERKEBUNAN NUSANTARA XIV (PERSERO) MAKASSAR - Nur Rahmi (BJRM (Bongaya Journal of Research in Management), 2019)
This explanatory research tried to explain influence and causality relationship between variables training , leadership style , and work discipline to the performance of employees. The samples used for data collection in this study amounted to 134 employees and using by the simple random samplingtechnique. Analysis technique used in this research is analysis of multiple regression (multiple regression).The result showed that the training, the leadership style and work discipline simultaneously partially and simultaneously has a positive impact significantly to performance of employee. The determination showed (R2) 0,996 or that is equal 99,6 %. Employee performance. Training, leadership he style and work dicipline also in partially has a positive impact significantly to performance of employee. The study it can be seen that the most dominant variable exacted on employee,s performance is work dicipline.